The association of time of emergency surgery – day, evening or night – with postoperative 30‐day hospital mortality. (27th August 2018) - Tessler, M. J.; Charland, L.; Wang, N. N.; Correa, J. A.
Summary: It is unclear whether the time of day for emergency surgery is associated with postoperative mortality. We assessed this association in 9319 patients who had emergency surgery as their first surgery at the Jewish General Hospital, Montreal, QC, Canada from April 2010 to March 2015. Of the 7362 (80%) patients with complete data, 168 (2.3%) died within 30 postoperative days. There was no significant association of time of day with postoperative mortality, with adjusted OR (95%CI) of 1.61 (0.96–2.72) for night vs. day, p = 0.07; 1.29 (0.78–2.13) for night vs. evening, p = 0.33; and 1.26 (0.89–1.78) for evening vs. day, p = 0.20. Studies of more patients and more factors, with longer follow‐up, should be carried out to exclude important associations of time of emergency surgery with postoperative mortality and morbidity.